1974
DOI: 10.1126/science.186.4167.934
|View full text |Cite
|
Sign up to set email alerts
|

Lesch-Nyhan Syndrome: Evidence for Abnormal Adrenergic Function

Abstract: Subjects with the Lesch-Nyhan syndrome (hypoxanthine-guanine phosphoribosyltransferase deficiency with self-mutilation) exhibit an apparently unique pattern of adrenergic dysfunction characterized by elevated plasma dopamine beta-hydroxylase activity and an absence of pressor response to acute sympathetic stimulation. Patients with a partial deficiency of hypoxanthine-guanine phosphoribosyltransferase without self-mutilation do not exhibit these abnormalities of adrenergic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Group I included subjects who rarely experienced hypotensive episodes with hemodialysis and group II consisted of patients who frequently have hemodialysis hypotension. Both groups of patients exhibited similar early hemodynamic responses to cold pressor tests, and these responses were similar to those previously observed in apparently healthy subjects (16,25). Although conclusions from these results must be tempered by the aforementioned limitations of the cold pressor test, the data suggest that hemodialysis-associated hypotension does not result from defective efferent sympathetic nerves or vascular abnormalities.…”
Section: Discussionsupporting
confidence: 70%
“…Group I included subjects who rarely experienced hypotensive episodes with hemodialysis and group II consisted of patients who frequently have hemodialysis hypotension. Both groups of patients exhibited similar early hemodynamic responses to cold pressor tests, and these responses were similar to those previously observed in apparently healthy subjects (16,25). Although conclusions from these results must be tempered by the aforementioned limitations of the cold pressor test, the data suggest that hemodialysis-associated hypotension does not result from defective efferent sympathetic nerves or vascular abnormalities.…”
Section: Discussionsupporting
confidence: 70%
“…The overresponse of children with Lesch-Nyhan syndrome to emotions of excitement or anger has suggested an excessive adrenergic response to some observers.292 In like manner, the self-mutilation, agitation, and "sham rage" produced by the methylated purines caffeine and theophylline as well as amphetamines furthered this type of speculation.52.228.240 More definitive evidence of an adrenergic overactivity has been provided by Rockson et al,267a who demonstrated a significantly increased activity of the enzyme dopamine-,Bhydroxylase in the plasma of all six patients tested who showed choreoathetosis and self-mutilation, while four less severely affected patients who showed neither of these symptoms despite deficient HPRT enzyme showed dopamine ,B-hydroxylase activities of plasma within the normal range. Since this enzyme is released into the synaptic cleft along with the neurotransmitter norepinephrine, the increased activity of the enzyme in plasma is thought to reflect an increased activity of the sympathetic nervous system.…”
Section: Adrenergic Dysfunctionmentioning
confidence: 92%
“…In contrast, NE levels have been reported to be normal or reduced at baseline, and irresponsive to postural changes (Lake and Ziegler 1977;Rockson 1974), or to exposure to cold (Rockson 1974). …”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, EPI concentrations have not been assessed in any of the published biochemical studies of LN disease (Rockson 1974;Lake and Ziegler 1977;Silverstein et al 1985;Jankovic et al 1988). In contrast, NE levels have been reported to be normal or reduced at baseline, and irresponsive to postural changes (Lake and Ziegler 1977;Rockson 1974), or to exposure to cold (Rockson 1974).…”
Section: Discussionmentioning
confidence: 99%